Weeds Enhance Multifunctionality in Arable Lands in South-West of France - Gaba, Sabrina; Cheviron, Nathalie; Perrot, Thomas; Piutti, Séverine; Gautier, Jean-Luc; Bretagnolle, Vincent (Frontiers in Sustainable Food Systems, 2020)
The current challenge in agriculture is to move from intensively managed to multifunctional agricultural landscapes that can simultaneously provide multiple ecological functions (multifunctionality), thus ensuring the delivery of ecosystem services important for human well-being. There is evidence that biodiversity is the main driver of multiple ecosystem functions. However, how biodiversity, and which components of biodiversity are the sources of multifunctionality, remain elusive. In the present study, we explore the role of weed richness and weed abundance as possible sources of ecosystem multifunctionality of an intensive agricultural landscape. Weeds are a key component of the arable field ecosystem trophic network by supporting various ecological functions while being a possible threat for production. We combine empirical data on ten ecosystem functions related to pollination, pest control and soil fertility, and measured across 184 fields cultivated with winter cereal, oilseed rape or hays in the Long Term Socio-Ecological Research site Zone Atelier Plaine & Val de Sèvre. We found that weed diversity was a strong contributor to multifunctionality in all crop types, especially when using the threshold-based approach. The effects of weed diversity were less pronounced for individual ecological functions except for weed seed predation and urease activity. As weeds may have dual effects on yields, we also explored the relationship between ecosystem multifunctionality and yield considering weed abundance. We however found a neutral relationship between yield and ecosystem multifunctionality. These results suggest that field management that maintains high levels of weed diversity can enhance multifunctionality and most ecological functions. Understanding how to maintain weed diversity in agricultural landscapes can therefore help to design sustainable management favoring the delivery of multiple services while maintaining food production. The next challenge will therefore be to assess the relative contribution of management practices, landscape features and weed diversity on ecosystem multifunctionality and yield.